Dimensão da agricultura familiar e periurbana no estado do Amapá: desafios para o abastecimento frente à urbanização - SEGOVIA, Jorge Frederico Orellana (Universidade Federal do Pará, 2019)
The study describes the particularities of small farms and the supply chains of major products from this segment of the Amapá State, measuring the conditions in which this productive sector is acting on, and the possibilities for which they can increase their participation in the marketplace. This includes information on prices, sales volumes, sales margins, marketing and the value of different segments involved in marketing. Based on this information we constructed an analysis of small farms in the state, showing their contribution to the different segments of the state economy. Was calculated the impacts of the produce agriculture would have in the marketing chain state. The main results refer to the importance of the family farming sector, responsible for agricultural production in the State Amapá, mainly of food crops, vegetables, fresh fruits, fruit pulps, black pepper and charcoal. While on the one hand, this sector had only a small share in the GDP from 2009, indicating that retail markets (supermarket chains and local farmer´s markets) were not as important with respect to the power of linking their supply chains. We also observed that family farming has been fulfilling some basic functions in the economy, focusing the sale of their products to the state funded farmer´s markets where the profit margins are much higher, and the remainder being sold at local retail stores. Thus familial agriculture contributes to the market supply and generation of employment and income in rural areas. Therefore, a need for the continuation of state subsidies along with reorienting and strengthening of its policies to this productive sector in order to promote their development in a more sustainable manner.